Disseminated actinomycetoma due to Nocardia wallacei. (5th February 2018) - Welsh, Oliverio; Salinas‐Carmona, Mario C.; Brown‐Elliott, Barbara A.; Smith, Terry; Cardenas‐De La Garza, Jesus A.; Wallace, Richard J.
Abstract: Background: Actinomycetoma caused by Nocardia usually responds well to antibiotics. Emerging species of Nocardia, such as N. wallacei, can be a therapeutic challenge. Aims: Confirm the therapeutic effectivity of linezolid in multidrug resistant Nocardia Wallacei actinomycetoma. Materials and Methods: We evaluated the medical management of an 18‐year‐old man with multidrug resistant actinomycetoma of the left leg caused by N. transvalensis complex treated 17 years ago with linezolid 1200 mg a day. This bacteria was recently reclassified as Nocardia Wallacei by specific molecular biology technique. Results: The infection was cured after 3 months of treatment; the patient remained asymptomatic for the past 17 years. No adverse effects were found. Discussion: Frequently, strains of N. transvalensis complex have aminoglycoside resistance; in this case, we highlight the effectiveness of linezolid for the successful medical management of multidrug resistant actinomycetoma. Conclusion: Linezolid can be an alternative for the treatment of multidrug resistant Nocardia Wallacei .